Dynamics of partially collapsing pulsed fluidized bed. (21st July 2021) - Ali, Syed Sadiq; Hossain, S. K. Safdar; Asif, Mohammad
Abstract: The use of flow pulsation as an effective assisted fluidization technique has been suggested in a number of applications, such as drying of food and pharmaceutical products, dry beneficiation of coal, and deagglomeration of nanopowders, owing mainly to its cost‐effectiveness and ease of implementation. The efficacy of this technique is, however, greatly affected by the frequency of pulsation since it controls the collapse dynamics of the fluidized bed. In this study, using ultrafine hydrophilic nanosilica with strong agglomeration tendencies, the pulsation frequency was controlled to allow only partial collapse of the bed between two successive pulsations while the global and local dynamics in different bed regions were carefully monitored. Besides the usual advantages associated with assisted fluidization techniques, such as lower minimum fluidization velocity, higher bed expansion, and elimination of bed non‐homogeneities, the continuous and intense solid motion imparted by the partial bed collapse caused a more substantial increase in the overall pressure drop than the one obtained with the conventional unassisted fluidization. The results of the frequency domain analysis highlighted the fact that the effect of pulsation event was felt differently in different regions of the bed depending upon the amplitude of the pulsation. These results were further corroborated by the similarity analysis.